2021
DOI: 10.3390/ijms22105394
|View full text |Cite
|
Sign up to set email alerts
|

CRL4-DCAF12 Ubiquitin Ligase Controls MOV10 RNA Helicase during Spermatogenesis and T Cell Activation

Abstract: Multisubunit cullin-RING ubiquitin ligase 4 (CRL4)-DCAF12 recognizes the C-terminal degron containing acidic amino acid residues. However, its physiological roles and substrates are largely unknown. Purification of CRL4-DCAF12 complexes revealed a wide range of potential substrates, including MOV10, an “ancient” RNA-induced silencing complex (RISC) complex RNA helicase. We show that DCAF12 controls the MOV10 protein level via its C-terminal motif in a proteasome- and CRL-dependent manner. Next, we generated Dc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 109 publications
(154 reference statements)
1
16
0
Order By: Relevance
“…A retroviral construct expressing eGFP-CENPB was a gift from Iain Cheeseman (pKG141-eGFP-CENPB; Addgene plasmid #69759). The cDNA library of the ubiquitin ligases was prepared as described previously ( Lidak et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…A retroviral construct expressing eGFP-CENPB was a gift from Iain Cheeseman (pKG141-eGFP-CENPB; Addgene plasmid #69759). The cDNA library of the ubiquitin ligases was prepared as described previously ( Lidak et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The motif is necessary and sufficient for ubiquitination of their hosts and was described as the canonical degron recognized by DCAF12 (Koren et al , 2018 ). Additional DCAF12 substrates were however later identified that do not harbor di‐Glu degrons (Cho et al , 2020 ; Lidak et al , 2021 ). DCAF12 downregulates MOV10, an RNA helicase involved in post‐transcriptional gene silencing, during T cell development and spermatogenesis (Lidak et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional DCAF12 substrates were however later identified that do not harbor di‐Glu degrons (Cho et al , 2020 ; Lidak et al , 2021 ). DCAF12 downregulates MOV10, an RNA helicase involved in post‐transcriptional gene silencing, during T cell development and spermatogenesis (Lidak et al , 2021 ). Recognition is mediated by the Glu‐Leu end of MOV10, and a range of proteins with noncanonical Glu‐Leu degrons appear to be substrates of DCAF12 (Koren et al , 2018 ; Lidak et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…All three modules are weakly positively correlated with seroconversion. Key regulator DDB1 and CUL4 associated factor 12 ( DCAF12 ) is an ubiquitin ligase and controls spermatogenesis and T-cell activation ( Figure S15E ) (Lidak et al 2021). DCAF12 has also been identified as being differentially expressed between high and low responders after hepatitis B vaccination (Bartholomeus et al 2018).…”
Section: Resultsmentioning
confidence: 99%